2017
DOI: 10.1038/srep44689
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates ICAM-1 expression and monocyte adhesiveness to TNF-α-treated endothelial cells: evidence for an anti-inflammatory cascade mediated by the miR-221/222/AMPK/p38/NF-κB pathway

Abstract: Resveratrol, an edible polyphenolic phytoalexin, improves endothelial dysfunction and attenuates inflammation. However, the mechanisms have not been thoroughly elucidated. Therefore, we investigated the molecular basis of the effects of resveratrol on TNF-α-induced ICAM-1 expression in HUVECs. The resveratrol treatment significantly attenuated the TNF-α-induced ICAM-1 expression. The inhibition of p38 phosphorylation mediated the reduction in ICAM-1 expression caused by resveratrol. Resveratrol also decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 38 publications
5
46
1
Order By: Relevance
“…In human monocytes, we found that all tested fractions or compounds of VOO reversed the reduction of SIRT1 gene expression caused by LPS. Our results match with those referred to the polyphenol resveratrol in TNF‐α treated human endothelial cells (Liu et al, ). Furthermore, we observed that the gene expression profile for PPAR γ was similar as to SIRT1 ; the UF, PF, and HTyr not only restoring but also potentiating PPAR γ gene expression in LPS‐treated human monocytes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In human monocytes, we found that all tested fractions or compounds of VOO reversed the reduction of SIRT1 gene expression caused by LPS. Our results match with those referred to the polyphenol resveratrol in TNF‐α treated human endothelial cells (Liu et al, ). Furthermore, we observed that the gene expression profile for PPAR γ was similar as to SIRT1 ; the UF, PF, and HTyr not only restoring but also potentiating PPAR γ gene expression in LPS‐treated human monocytes.…”
Section: Discussionsupporting
confidence: 91%
“…In human monocytes, we found that all tested fractions or compounds of VOO reversed the reduction of SIRT1 gene expression caused by LPS. Our results match with those referred to the polyphenol resveratrol in TNF-α treated human endothelial cells (Liu et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…A recent clinical trial involving primary hypertensive patients evidenced that addition of a micronized formulation of RSV to standard antihypertensive therapy is sufficient to normalize the blood pressure, without additional antihypertensive drugs [127]. Other targets of RSV were identified by different other groups: TLR4 [128,129], miR-221/222 [130] and p38 MAPK [131,132].…”
Section: Stilbenesmentioning
confidence: 99%
“…In addition, SIRT1 suppresses the NF-κB signaling pathway, thereby acting as an anti-inflammatory agent in persons with atherosclerosis, a chronic inflammatory disease (12). Interestingly, the SIRT1 activator resveratrol inhibits ICAM-1 expression in endothelial cells (13), Th2 cytokine expression in mast cells (14), and interleukin (IL)-1β-induced expression of matrix metalloproteinase-13 and IL-6 in articular chondrocytes (15). In addition, resveratrol decreases nitric oxide synthesis by hepatocytes (16), which suggests that SIRT1 activation by resveratrol ameliorates inflammation.…”
Section: Introductionmentioning
confidence: 99%